Исследование особенностей организации систем единого входа. ЧАСТЬ 1: Модель представления данных и идентификации в сервисных подсетях - Зеленцова, Ж. Ю.; Йона, Е. О. (НТУ "ХПИ", 2014)
С ростом количества сервисов в глобальной сети возникает необходимость их агрегации. Показано, что существует несколько подходов «бесшовного» объединения сервисов в пользовательском сегменте сети. Отмечено, что остается открытым вопрос организации единого доступа к сетевым сервисам. Обосновывается необходимость введения систем идентификации и обеспечения доступа с единым входом. Рассмотрена модель представления данных, что сочетает фиксацию сведений о пользователях, их устройствах и действиях в глобальной сети.

As the number of services in a global network aggregation is necessary. It is shown that there are several approaches «seamless» association services in the custom network segment. It is noted that the question remains the single process of access to services. The necessity of the introduction of systems to identify and provide access to the SSO. We consider the model of data that combines fixation information about users, their devices, and actions in a global network. An approach to protect public depositories of connected data about network users. A variant of solving the problem of large data using data binding model iGenotype network. We propose a two-stage method of identification based on endo-and ekzopatterna in the public service and the trusted zone subnets. Proposed a model of the data, which involves the expansion of unified SLA-queries. It is shown that the unification of queries reduces the complexity of the service system, and also allows us to describe the process of providing services within the framework of the modern approach to service delivery SLA-requests.
Research features iam systems. PART 1: Data and identification model of service subnets
Keywords: организация доступа; глобальная сеть; агрегация; IAM; Single Sign-On; iGenotype; e-passport